2010
DOI: 10.1111/j.1445-2197.2009.05092.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐port laparoscopic right colonic resection

Abstract: Single-port laparoscopic techniques can be applied to colonic surgery. It negates morbidity associated with trochar insertion and port sites. It should be performed by surgeons familiar with laparoscopic colorectal techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The technique has been employed successfully for a number of colorectal procedures, including right hemicolectomy [2,4,6,8,9,[20][21][22][23][24][25], total colectomy [26][27][28], proctocolectomy with ileal pouch anal anastomosis [28,29], and left colectomy [2,25,30]. Several case reports and series have been published involving use of the SILC technique for sigmoid resection [3,7,[31][32][33][34][35][36][37][38], the largest of which included 10 consecutive patients who underwent resection for recurrent diverticulitis [38].…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been employed successfully for a number of colorectal procedures, including right hemicolectomy [2,4,6,8,9,[20][21][22][23][24][25], total colectomy [26][27][28], proctocolectomy with ileal pouch anal anastomosis [28,29], and left colectomy [2,25,30]. Several case reports and series have been published involving use of the SILC technique for sigmoid resection [3,7,[31][32][33][34][35][36][37][38], the largest of which included 10 consecutive patients who underwent resection for recurrent diverticulitis [38].…”
Section: Discussionmentioning
confidence: 99%
“…At present, single-port laparoscopic colectomy is performed with a commercially available portaccess device, which is inserted by a small transumbilical incision. After initial case reports on single-port colectomy [3][4][5][6][7][8][9][10], there are 16 case series [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] in the literature to date, providing level IV evidence ( Table 2). Two reports describe single incision colectomy with multiple trocars through one umbilical incision [16,17], but most groups use commercially available port-access devices [11][12][13][14][15][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…For malignant disease, all surgical margins were negative, with at least the required minimum of 5 cm, in both groups. On pathological examination, there were three adenomas and three early malignant tumours (pT1N1, pTisN0, pTisN0) in the single-port colectomy group, with a median of 12 retrieved lymph nodes (range [8][9][10][11][12][13][14][15][16][17]. The number of lymph nodes extracted in the malignant specimen was 12, with one positive node.…”
Section: Operative Outcomesmentioning
confidence: 99%
“…The benefits of laparoscopic surgery for colorectal resection are well reported but a standard multiport technique still carries the risk of trocar-related injury, haemorrhage and hernia. This has led to the development of single port techniques which have to date been used for surgery to the appendix, gallbladder, kidney and most recently the colon [9][10][11][12][13][14][15]. A recent systematic review by Makino et al [13] has shown that single incision laparoscopic right colectomy is safe and feasible when performed by skilled laparoscopic surgeons.…”
Section: Discussionmentioning
confidence: 99%